دور المجالس المحلية الجزائرية في تجسيد التنمية المحلية المستدامة - سعد االله السعيد . - عزيزي الزهرة (جامعة المسيلة, 2024)
إن الحدیث عن التنمیة الوطنیة الشاملة والمستدامة یقتضي حتمیا للحدیث عن التنمیة المحلیة تلك التي تراعي الأبعاد الخصوصیة للإقلیم المحلي من جهة وقطاعات المجتمع المحلي من جهة أخرى، ولقد سعت الجزائر منذ الاستقلال إلى یومنا هذا إلى تدعیم البلدیة وجعلها أداة للتنمیة المحلیة باعتبارها أقرب إلى معرفة الحاجات المحلیة والأقدر على تجسیدها وتنفیذها بحكم اتصالها المباشر مع المصالح المحلیة . إن التنمیة المحلیة المستدامة تتحقق بتكاثف الجهود الشعبیة والحكومیة، وهذا ما یتمثل أساسا في الدور الفعال الذي تلعبه البلدیة من خلال تشجیعها للقطاع الخاص والمؤسسات الصغیرة والمتوسطة ودعم قطاع الفلاحة وبالتالي تخفیض البطالة، كما تساهم في مكافحة الفقر عن طریق توفیر الرعایة الصحیة الكاملة للسكان المحلیین وضمان السكنات لهم وغیرها من الخدمات الاجتماعیة، كما لها دور مهم في مكافحة الأمیة فهي الداعم الأساسي لرفع الكفاءة الثقافیة بتفعیل النشاطات الثقافیة والریاضیة وتولي أهمیة للقطاع السیاحي من خلال الاهتمام بالمعالم الأثریة والتار یخیة والمناطق الترفیهیة. Summary: Talking about comprehensive and sustainable national development inevitably requires talking about local development that takes into account the specific dimensions of the local region on the one hand and the sectors of local society on the other hand. Algeria has sought, from independence to the present day, to strengthen the municipality and make it a tool for local development as it is closer to knowing local needs. It is best able to embody and implement it by irtue of its direct connection with local interests. Sustainable local evelopment is achieved by intensifying popular and governmental efforts, and this is mainly represented in the effective role played by the municipality by encouraging the private sector and small and edium enterprises and supporting the agricultural sector and thus reducing unemployment. It also contributes to the fight against overty by providing full health care to the local population and ensuring housing. They and other social services, and it also has an important role in combating illiteracy, as it is the primary supporter of raising cultural competence by activating cultural and sports activities, and it attaches importance to the tourism sector by paying attention to archaeological and historical monuments and recreational areas.